Utilização de informações genômicas para o melhoramento genético de características da carne em bovinos da raça Nelore - Magalhães, Ana Fabrícia Braga [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Consumers have become stricter for higher quality meat and are seeking for traits such as tenderness, color and flavor. Few has been done for improving meat quality traits, due to the difficultness and high cost to measure, as well as to the necessity of culling animals. An alternative to inclusion of these measures in breeding programs may be the use of SNPs in association studies and genomic selection. Animals Nellore (1,875) were feedlot finished and slaughtered at commercial slaughterhouses were used, with an average age of 731 ± 81 days. The samples were analyzed for tenderness, lipid content, marbling, lightness (L*), redness (a*) and yellowness (b*). The animals were genotyped with a panel of 777,962 SNPs (IlluminaBovineHDBeadchip) and after quality control remained 1,634 animals with genotypes and 369,722 SNPs. In chapter 2, three genomic selection methods were evaluated: GBLUP (assumes normal distribution with variance only for all SNPs effects), BayesCπ (mixed distribution to the SNPs effects) and Bayesian Lasso (assumes double exponential distribution for SNPs effects). The adjusted phenotype for the fixed effects (Yc) and the estimated breeding value (EBV) were used as pseudo-phenotypes. For cross-validation, the population was randomly divided into five groups of similar sizes. To compare the predictive ability of the methods, the following procedures were used: correlation between the genomic values (GEBV) and the adjusted phenotypes and the correlation value divided by the square root of the heritability; correlation between EBV and GEBV; regression coefficient of the GEBV on adjusted phenotype and GEBV on EBV. The EBV as pseudo-phenotype was more accurate than the adjusted phenotype. The GBLUP showed better predictive ability for meat color. For the other traits, the Bayesian methodologies had higher predictive ability. Among the Bayesian methodologies, BayesCπ was more accurate than Lasso for all traits. In Chapter ...

O consumidor tem se tornado mais exigente com relação a qualidade da carne, fatores como maciez, cor e sabor são as características mais requeridas. Pouco tem sido feito em relação à qualidade da mesma, pois essas características não são consideradas nos programas de avaliação genética para gado de corte no Brasil, por serem de mensuração difícil, alto custo, e por exigir o abate dos animais. Uma alternativa para inclusão destas medidas em programas de melhoramento pode ser o uso dos SNPs em estudos de associação e seleção genômica. Foram utilizados 1.875 animais machos da raça Nelore foram terminados em confinamento e abatidos em planta frigorífica comercial, com idade média de 731±81 dias. As amostras coletadas foram analisadas para maciez, lipídeos, marmoreio, coloração L* (luminosidade), a* (vermelha) e b* (amarela). Os animais foram genotipados com um painel de 777.962 SNPs (Illumina BovineHD Beadchip) e após o controle de qualidade restaram 1.634 animais com genótipos e 369.722 SNPs. No capítulo 2, três métodos de seleção genômica foram avaliados: GBLUP (assume distribuição normal com variância única para todos os efeitos de SNPs), BayesCπ (apresenta uma distribuição mista para os efeitos dos SNPs) e Bayesian Lasso (assume distribuição dupla exponencial para os efeitos dos SNPs). O fenótipo corrigido para os efeitos fixos (Yc) e o valor genético predito (EBV) foram utilizados como pseudo-fenótipos. Para a validação cruzada, a população foi dividida aleatoriamente em cinco grupos de tamanhos similares. Para comparar a habilidade de predição dos métodos foram calculadas: a correlação entre os valores genômicos (GEBV) e os fenótipos corrigidos e o valor da correlação dividido pela raiz quadrada da herdabilidade; a correlação entre GEBV e EBV; o coeficiente de regressão do GEBV sobre o fenótipo corrigido e do GEBV sobre o EBV. O EBV como pseudo-fenótipo foi mais acurado...
Keywords: Bovino de corte; Nelore (Zebu); Carne bovina; Genômica; Bovino - Melhoramento genetico; Marcadores genéticos; Genomics